X-ray Surveys of the Hot and Energetic Cosmos. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Comastri, Andrea; Urry, C. Megan
Abstract: A science meeting is an opportunity to exchange ideas with colleagues, to hear of new results and to learn from comprehensive reviews of a topic. Much of it happens in the meeting room and much of it also happens in the corridors of the meeting venue and in restaurants and perhaps bars near the meeting location. Its a combination of people and of place that is a bit [hard to predict] but when it goes well, you know it. All these elements came together for IAU Focus Meeting 6, X-ray Surveys of the Hot and Energetic Cosmos, in Honolulu last August. There are not many places more pleasant for an astronomical meeting than Hawaii, and the speakers did an outstanding job of reviewing the field and relaying the latest results. X-ray surveys have been a staple of astrophysics for nearly 50 years. There are large surveys and small, deep surveys and shallow, soft X-ray energies and hard. The combination gives us invaluable information about the hottest and/or most relativistic environments known. Theory helps us interpret the data in terms of the underlying physics. The heady combination of all of the above shaken and mixed in Hawaiian paradise has given us all a deeper understanding of the Universe. Please read on to see why.